Experience Of Developed Countries In Financial Support For Preschool Education - Khayitbayevna, Turdiyeva Yakitjan (Innovative Technologica: Methodical Research Journal, 2024)
The article examines the experience of developed countries in financing preschool education and its application in Uzbekistan. It emphasizes the importance of investments in early childhood development, as key competencies, such as personal and cognitive skills, are formed during the preschool education stage. The mechanisms of state investments in the preschool education sector are also explored.